The role of social media in promoting the cultural identity of Saudi society (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to explore the role of social media in promoting the cultural identity of Saudi society, focusing on the statistical impact of usage dimensions (diversity, interaction, purposeful use, content awareness) on identity aspects (pride, heritage knowledge, value preservation, intergenerational transmission). Adopting a descriptive-analytical and qualitative approach, data were collected via an electronic questionnaire validated through literature review, face validity, and reliability tests. A simple random sample of 384 social media users in Saudi Arabia was selected using Krejcie and Morgan’s formula. Data were analyzed via SPSS (v25) using descriptive statistics, Pearson’s correlation, Cronbach’s alpha, and multiple linear regression. Results revealed a strong positive impact of social media use on cultural identity enhancement (R²=0.810), with "purposeful use" being the most influential dimension (Beta=0.480). Challenges included the marginalization of Arabic (mean=3.37) and weak content oversight (mean=3.27). Recommendations emphasized supporting authentic cultural content production, promoting digital literacy, and enhancing the role of families and educational institutions in guiding youth toward positive social media engagement.
Keywords: Social Media; Cultural Identity; Saudi Society